Too much and never enough : how my family created the world's most dangerous man - Trump, Mary L. (Simon & Schuster, 2020)
"Mary L. Trump, a trained clinical psychologist and Donald's only niece, shines a bright light on the dark history of their family in order to explain how her uncle became the man who now threatens the world's health, economic security, and social fabric"--Provided by publisher.